Revolutions in military affairs that did not occur: A framework for analysis. Issue 5 (19th October 2016) - Fridman, Ofer
ABSTRACT: The existing literature suggests different ways to explain the interconnection between technology, military, and society that creates changes in military affairs. It seems, however, that most of this literature concentrates on successful cases of military transformations and overlooks a significant number of failed transformations. The purpose of this article is to define the conceptual social-political-military environment that creates, or not, military transformations in general, and revolutions in military affairs (RMAs) in particular. Supporting its argument with two historical examples, this article suggests that an RMA is an outcome of traceable imbalance between political leadership, its military, and unmet political-military challenges. The conceptual framework proposed by the article significantly improves the ability of scholars and practitioners to explore, explain, and anticipate the possible directions of military transformations by a systematic examination of the political-military challenges that these transformations are intended to bridge and the socio-cultural environments that shape political-military decision-making processes.